Magnitude of malnutrition and associated factors among HIV infected children attending HIV-care in three public hospitals in East and West Gojjam Zones, Amhara, Northwest, Ethiopia, 2017: a cross-sectional study - Yihenew Sewale (BMC Research Notes, 2018)
Abstract Objective The main aim of this study was to assess the magnitude of malnutrition and associated factors among HIV infected children in Amhara Regional State, and Northwest Ethiopia. This study is a result of single observation. Results A total of 372 study participant were interviewed, of which 60.2%, 95% CI (55.90–65.60) were malnourished. Children who had good individual dietary diversity were 53% times less likely malnourished as compared to children who had fair/poor dietary diversity (AOR = 0.474, 95% CI (0.26, 0.86)). Sex of child, Age of the child, undiversified diet, comorbidity disease, oral ulcer, diarrhea and history of hospital admission were found statically significant associated with malnutrition. Magnitudes of malnutrition among HIV infected children were very high. The early detection and control progression of HIV, closely follow up to intervene this situation is highly recommended.